Natural Resources Management 2017
DOI: 10.4018/978-1-5225-0803-8.ch069
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Learning and Gradual Changes

Abstract: The environmental consequences of climate change in agriculture have been degrading farmers' livelihood and welfare because of their inability to cope with the unusual risks and livelihood crises due to climate change. However, state policies addressing farmers' needs to develop their coping mechanism towards the unusual consequences of climate change have not been defined appropriately. To continue relying on their conventional ways of farming would not effectively help them to survive in the midst of unusual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Under an electric potential, water molecules are packed more tightly, and thus, the water flow is impeded, as observed for water in carbon nanotubes under electric fields. 33 In AV membrane, salt rejection is the lowest (∼50%) among the eight membranes. As shown in Figure S3, when the ions permeate from the left to right of the AV membrane, an electric potential is generated by the ions and is opposite to the one generated by dipeptides.…”
Section: Water Diffusionmentioning
confidence: 94%
“…Under an electric potential, water molecules are packed more tightly, and thus, the water flow is impeded, as observed for water in carbon nanotubes under electric fields. 33 In AV membrane, salt rejection is the lowest (∼50%) among the eight membranes. As shown in Figure S3, when the ions permeate from the left to right of the AV membrane, an electric potential is generated by the ions and is opposite to the one generated by dipeptides.…”
Section: Water Diffusionmentioning
confidence: 94%
“…As shown in Figure S14B, the average number of H-bonds per water molecule shows a local maximum (3.70−3.76) when the planar water layers are formed at d = 6, 8, 11, and 13 Å. To investigate the dynamic nature of H-bonds we calculated the Hbond correlation function 41,42 defined as C HB (t) = ⟨h(0)h(t)⟩/ ⟨h⟩ where h(t) = 1 when a tagged water molecule at time zero is bonded to the same H-bond partner molecule at time t, and h(t) = 0 otherwise. The C HB (t) shows a fast initial decay within 1 ps and then an extremely slow decay at longer times (Figure S15).…”
Section: ■ Methodsmentioning
confidence: 99%
“…A further study of TIP4P water inside a wider (3,15) singlewalled CNT (d = 1.31 nm) 268 observed populations of three different polygonal ice nanotubes modulated by both temperature and E-field along the pore axis. An exploration of the effect of axial E-fields on the structure of SPC water in CNTs from (7,7) to (10,10) 269 showed that E-fields of 1−2 V/nm along z induced a transition from liquid to ice nanotubes. Similarly, simulations of SPC and of TIP4P waters in a (8,8) CNT 270 showed that an axial E-field of 1 V/nm caused water to form a solid-like structure at all simulation temperatures up to 350 K. This suggested that the E-field induced a phase transition from liquid to ice-nanotube.…”
Section: Cntsmentioning
confidence: 99%
“…An exploration of the effect of axial E-fields on the structure of SPC water in CNTs from (7,7) to (10,10) 269 showed that E-fields of 1−2 V/nm along z induced a transition from liquid to ice nanotubes. Similarly, simulations of SPC and of TIP4P waters in a (8,8) CNT 270 showed that an axial E-field of 1 V/nm caused water to form a solid-like structure at all simulation temperatures up to 350 K. This suggested that the E-field induced a phase transition from liquid to ice-nanotube. Applying a high piston pressure (∼500 MPa) can lead to water flow though the CNT even in the presence of an axial electrostatic field.…”
Section: Cntsmentioning
confidence: 99%